Impact of the Surgical Approach to Thymectomy Upon Complete Stable Remission Rates in Myasthenia Gravis: A Meta-analysis. (27th July 2021) - Solis-Pazmino, Paola; Baiu, Ioana; Lincango-Naranjo, Eddy; Trope, Winston; Prokop, Larry; Ponce, Oscar J.; Shrager, Joseph B.
Abstract : Objectives: To determine whether the available operative techniques for thymectomy in myasthenia gravis (MG) confer variable chances for achieving complete stable remission (CSR), we performed a meta-analysis of comparative studies of surgical approaches to thymectomy. Methods: Meta-analysis was done of all studies providing comparative data on thymectomy approaches, with CSR reported and minimum 3-year mean follow-up. Results: Twelve cohort studies and 1 randomized clinical trial, containing 1, 598 patients, met entry criteria. At 3 years, CSR from MG was similar after video-assisted thoracoscopic (VATS) extended vs both basic (relative risk [RR] 1.00, p = 1.00, 95% confidence interval [CI] 0.39–2.58) and extended (RR 0.96, p = 0.74, 95% CI 0.72–1.27) transsternal approaches. CSR at 3 years was also similar after extended transsternal vs combined transcervical-subxiphoid (RR 1.08, p = 0.62, 95% CI 0.8–1.44) approaches. VATS extended approaches remained statistically equivalent to extended transsternal approaches through 9 years of follow-up (RR 1.51, p = 0.05, 95% CI 0.99–2.30). The only significant difference in CSR rate between a traditional open and a minimally invasive approach was seen at 10 years when the now-abandoned basic (non–sternum-lifting) transcervical approach was compared to the extended transsternal approach (RR 0.4, p = 0.01, 95% CI 0.2–0.8). Conclusions: A significant difference in the rate of CSR among various surgical approaches for thymectomy in MG was identified only at long-term follow-up and only between what might be considered the most aggressive approach (extended transsternal thymectomy) and the least aggressive approach (basic transcervical thymectomy). Extended minimally invasive approaches appear to have CSR rates equivalent to those of extended transsternal approaches and are therefore appropriate in the hands of experienced surgeons.